Pendampingan Pengelolaan BUMDes Maju Bersama dalam Rangka Optimalisasi Potensi Desa di Desa Cisempur, Kecamatan Jatinangor, Kabupaten Sumedang - Yahya, Afif Syarifuddin (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2024)
The government is obliged to fulfill the minimum needs of all citizens to live in prosperity, but many villagers live in poor conditions. One of the government’s efforts to overcome poverty is to form Village-Owned Enterprises (BUMDes) to manage businesses and utilize village assets based on the superior potential of the village. Even though it has been established since 2018, BUMDes Maju Bersama of Cisempur Village, has yet to be able to develop and has even tended to go bankrupt. Community service activities include assistance aimed at developing BUMDes businesses by optimizing the village’s potential. The method used is mentoring and participatory action research. The results of community service activities show that there are five problems, namely BUMDes, which do not yet have the status of a legal entity, do not have a secretariat office, do not have their place of business, financial and asset management is not good, and business fields that are less attractive to the public. To solved this problem, improvements have been made to BUMDes statutes and bylaws, accelerated rehabilitation of buildings for the secretariat office and location of business premises, improvement of financial and asset management, and expansion of business fields in financial services, waste management services, cart rental services, and primary food sales.